Peas in a cultural pod? A comparison of the skills and personal attributes of artists and musicians - Bennett, Dawn (Australian Society for Music Education, 2004)
This paper focuses on a project that compared characteristics between the working lives of musicians and a broad range of artists from the cultural industries, and is part of a larger study concerning the careers of instrumental musicians. The project consisted of two sets of interviews; the first with musicians, and the second with representatives from the cultural industries. Results are particularly significant to music educators in (i) establishing the relevance to musicians of a rich source of artist-related literature, including statistical data enables the use of these materials in advocacy, research and teaching, and (ii) the identification of factors considered crucial to the sustainability of careers in music that contribute to the development and delivery of vocationally-relevant music curricula at the school and tertiary levels.